2018
DOI: 10.1002/aelm.201700434
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Integrated and Multifunctional All‐Soft Physical Microsystems Based on Liquid Metal for Electronic Skin Applications

Abstract: of objects, as well as motions and gestures of the human body. [4,5] Moreover, the brain can interpret more sophisticated information to distinguish, for example, touch and pain, and eventually convey feelings and emotions. [4,5] Therefore, electronic skins (e-skins), which can mimic the capability of the sensory receptors of the human skin, can provide an improvement in the quality of life to people with skin damage or amputations by restoring these capabilities. [1,4,5] This motivation for e-skins has initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 58 publications
1
45
0
1
Order By: Relevance
“…The gallium films can be used to produce precise, repeatable, and durable sensing devices. To date, a large variety of sensors based on liquid metal conductors have been proposed to measure finger joint movements . However, most of these demonstrations were qualitative, restricted to single or mm‐thick devices, or performed on mock‐up hand models.…”
supporting
confidence: 78%
“…The gallium films can be used to produce precise, repeatable, and durable sensing devices. To date, a large variety of sensors based on liquid metal conductors have been proposed to measure finger joint movements . However, most of these demonstrations were qualitative, restricted to single or mm‐thick devices, or performed on mock‐up hand models.…”
supporting
confidence: 78%
“…Recently, we demonstrated high resolution, uniform, and residue‐free EGaIn thin‐line patterning ranging from single micrometer to millimeter scales by utilizing a chemical surface modification and residue transfer process in a reverse stamping approach to enable high‐density, soft passive electronics . Building on our previous work, this paper presents multiscale and uniform EGaIn thin‐film patterning by utilizing an additive stamping process for large‐scale (mm–cm) soft electronics and the subtractive reverse stamping process for microscale (µm–mm) soft electronics. By combining these complementary patterning techniques using 3D heterogeneous integration, fabricated and optimized soft electronic components built with different patterning processes can be integrated to form high‐density and multifunctional soft microsystems.…”
Section: Introductionmentioning
confidence: 95%
“…The dominant working principle of the liquid metal-based stretchable strain sensors is the geometrical effect. [167][168][169][170][171] In the following sections, it will be shown that the contribution of this mechanism to the overall sensing performance of nanomaterials-based stretchable sensors may not be significant.…”
Section: Geometrical Effectmentioning
confidence: 99%